Kebiasaan Konsumsi Makanan Berlemak, Jenis Persalinan dan Jenis Alat Kontrasepsi dengan Hasil Pemeriksaan IVA Test: Fatty Food Consumption Habits, Type of Delivery and Types of Contraceptive Devices with IVA Test Results - Astuti (Dohara POAJ, 2021)
Introduction: One of the efforts to challenge it is by conducting an IVA test. Some factors that increase the IVA test are consumption habits of fatty foods, the type of delivery and the type of contraception. The research objective was to study the relationship between fatty eating habits, the type of delivery and the type of contraception with the results of the examination of IVA tests at the Ministry of Home Affairs in 2020. Method: quantitative analytic research methods with cross sectional. Sample taking 269 respondents, total sampling technique sampling. Result: The results showed the fact that there is a relationship between consumption habits of fatty foods with IVA examination results with a P value of 0.048. There is a significant relationship between the types of labor with the results of the examination of IVA tests with a P value of 0.034. There is a significant relationship between the type of contraception with the results of IVA examination with a P value of 0,000. Discussion: Based on these results, it can be seen that with both vaginal and abdominal deliveries, the majority of the IVA test results were positive. This is due to the fact that the majority of respondents have little parity and the majority of the IVA test results are normal. In conclusion there is relationship between fatty eating habits, the type of delivery and the type of contraception with the results of IVA examination.